Industrial training report: Theta Edge Berhad / Muhamad Azim Mohd Idris - Mohd Idris, Muhamad Azim (Perpustakaan Tengku Anis, 2019)
The Industrial Training subject IMC690 provides pre-professional work experience with specific assignments and responsibilities. The student will be undergo the industrial training based on the period from 1 February 2019 to 28 June 2019 in Integration System Management (ISM), Tabung Haji Information Department at Theta Edge Berhad. To fulfil the faculty's requirement, students should involve in information management related work during their training. This might include areas such as library science, resource centre management, and records management and information management system. The student involve in the operation of ISM Team relate to the conducting system and bank request, fixing bugs and issue management and also server maintaining. Student can learn a lot of new thing that beyond the IM245 courses and also experience in real environment in the industry. Besides that, student also prepare and complete their special project to fulfil the IMC690 Industrial Training Subject.